NANO-ENABLED SYSTEMS FOR THE DELIVERY OF BERBERINE - Vinay Patil; Snehal Thakar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Berberine (BBR) is an alkaloid that belongs to isoquinoline functional group which is further classified as protoberberines. From ancient times it has been utilized in hyperlipidaemia & diabetes type II. Various studies performed on Berberine has proved it acts as anticancer by mode of cell necrosis. Due to poor water solubility & minimal bioavailability Berberine fails as effective chemotherapeutic agent. The drug has been combined with other antineoplastic agents to improve activity, but the results were not impressive. Use of adjuvant therapy cannot withstand in today’s era, as co-administration may further lead to pharmacological complication in biological system. Nanosizing of Berberine as single bullet or in combination with well-known antineoplastic agent can help to improve distribution & target-based release of chemotherapeutic agents into carcinogenic tissue. In this chapter detailed description, ancient background of Berberine & its application as antineoplastic delineate & importance of nano enabled Berberine is summarized.